Features of loan disbursement at matlab RDP during 1992-1995 - Hussain, Shahed; Moore, Karen (BRAC, 2019)
BRAC's credit programme forms the core of the Rural Development Programme (RDP), itself the central programme of BRAC's development interventions. In the context of the BRAC - ICDDR,B Joint Research Project in Matlab, it is important to have a clear picture of BRAC' s credit activities in Mat lab to understand the impact of BRAC and its programmes on the health and well-being of the rural poor. This study provides a preliminary understanding of the structure of BRAC' s loan portfolio in Mat lab during 1992-1995, focusing on the following areas: membership growth, loan portfolio growth, loan repayment, average loan size, and the distribution of loans between loan type, sector and scheme. Analysis indicates that in Matlab, membership and loan portfolio growth rates have been slower than in other area offices of the same age. This may be due to difficult communication in the area. After 1995, growth rates of membership and loan disbursement have improved. Matlab RDP showed no overdue loans and negligible late loans during the study period. For these reasons, Matlab RDP can be considered a successful BRAC area office. Average loan size increases with the number of loans taken, but after the third loan the: increase was less significant. Multiple and concurrent loans were not common. During the study period, loans in Matlab were predominantly targeted towards agricultural activities: 44.1% of the total loan was used for agricultural activities, primarily for those which were not supported by BRAC training and inputr5. Small scale trading was the second significant destination for BRAC credit at 26.7%, and 9.8% went towards transport activities, predominantly rickshaws. These three largest credit destinations reflect the Matlab environment where agriculture and trade, particularly in fruits and vegetables, is the major source of employment, and communication is difficult. It is recommended that the information regarding credit in Matlab should be gathered in a more coordinated way, so that the distribution of loans can be monitored in such a way that Matlab's status, compared to other BRAC area offices can be clearly noted. This is particularly relevant for monitoring the growth in targeted Employment and Income Generating sectors, which · had not been major loan destinations in Mat lab to the end of 1995.